Seneca’s Heraclitus DK 22 B 49a and Parmenides - Franchi, Leonardo (Peitho. Examina Antiqua, 2024)
Several scholarly inquiries have explored the possibility that Parmenides was acquainted with Heraclitus and engaged in polemics against him, in light of the fact that their respective chronologies do not preclude this scenario. However, with few exceptions, the debate remains polarized between two main positions: the first contends that Heraclitus and Parmenides were likely unaware of each other, or at least that no conclusive evidence exists to prove their acquaintance; the second posits that Parmenides was indeed aware of Heraclitus and argued against him. This paper focuses on Heraclitus B 49a DK to offer additional, albeit measured, support for the latter position and to suggest a hypothesis, at least a partial one, concerning the origins of Parmenides’ κρίσις between εἶναι and μὴ εἶναι.